Role of the Mitochondrial Protein Import Machinery and Protein Processing in Heart Disease - Zhao, Fujie; Zou, Ming-Hui (Frontiers in Cardiovascular Medicine, 2021)
Mitochondria are essential organelles for cellular energy production, metabolic homeostasis, calcium homeostasis, cell proliferation, and apoptosis. About 99% of mammalian mitochondrial proteins are encoded by the nuclear genome, synthesized as precursors in the cytosol, and imported into mitochondria by mitochondrial protein import machinery. Mitochondrial protein import systems function not only as independent units for protein translocation, but also are deeply integrated into a functional network of mitochondrial bioenergetics, protein quality control, mitochondrial dynamics and morphology, and interaction with other organelles. Mitochondrial protein import deficiency is linked to various diseases, including cardiovascular disease. In this review, we describe for the first time an emerging class of protein or genetic variations of components of the mitochondrial import machinery involved in heart disease. The major protein import pathways, including the presequence pathway (TIM23 pathway), the carrier pathway (TIM22 pathway), and the mitochondrial intermembrane space import and assembly machinery, related translocases, proteinases, and chaperones, are discussed here. This review highlights the importance of mitochondrial import machinery in heart disease, which deserves considerable attention, and further studies are urgently needed. Ultimately, this knowledge may be critical for the development of therapeutic strategies in heart disease.